Safety-Oriented Optimization of Polymer Components in FDM Using MCDM - Subramani, Raja; Rusho, Maher Ali; Wahhab Ibraheem, Shahad Abdul; Ahmed, Hassan Safi; Al-Adily, Kareem; Ali, Mohsin; Rahmani, Maha H. Philip; Mustafa, Mohammed Ahmed; Ismael, Tholfiqar Najah (Journal of Research Updates in Polymer Science, 2025)
Fused deposition modeling (FDM) has become a widely adopted additive manufacturing method for producing functional polymer components across industrial and biomedical domains. However, ensuring both mechanical performance and safety reliability remains challenging due to the sensitivity of FDM outcomes to process parameters. This study proposes a decision-making framework integrating Fuzzy Analytic Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to optimize FDM process parameters—layer thickness, infill density, print speed, and extrusion temperature—based on mechanical and safety performance indicators. Experimental and decision analyses identified an optimal configuration of 0.2 mm layer thickness, 80% infill density, 60 mm/s print speed, and 220 °C extrusion temperature, resulting in a 17.6% improvement in tensile strength and a 14.3% increase in safety factor, calculated as the ratio of maximum tensile stress to yield stress, compared to baseline settings. The proposed framework provides a systematic pathway for balancing mechanical integrity and safety reliability in polymer additive manufacturing, offering practical value for industrial optimization and sustainable design.